Strategi Pengembangan Agribisnis Gula Aren Di Kabupaten Sekadau - Radian, Suryansyah, Nurliza, (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2018)
Aren is a type of palm that has a highly potential economic value. Semabi, Sekadau Hilir Sub-district is the largest producer in the District of Sekadau; however, it is only processed to produce molded sugar. This study aimed to formulate a strategy for the palm sugar agrybusiness development in Sekadau District. The research method was a quantitative descriptive, and the data were processed using IFE/EFE, SPACE and SWOT. The values obtained from IFE and EFE matrixes were 2.57 and 2.65 respectively. From the SWOT analysis, alternative strategies were obtained, namely, SO Strategy: expanding the location of the area sugar palm cultivation, increasing production capacity, and improving the quality of product. WO Strategy: increasing of human resources (farmers), developing a partnership and developing a market information network. ST Strategy: government policies that supporting, increasing the added value and production. WT Strategy: building a support facility of sugar palm agribusiness, increasing coordination and cooperation among stakeholders in strengthening palm agribusiness, and increasing marketing and promotion for the expansion. Keyword: Aren (palm), agrybusiness, IFE/EFE matrixes, SPACE matrix, and SWOT analysis.